Thinking Thoughts. - Armour, Phillip G. (Communications of the ACM, 2015)
The article presents the author's thoughts and opinions on software design and the relationship between human beings and computers. The author discusses human consciousness, which is the human capacity to reflect on thinking. The article discusses the ways that humans process information and store this knowledge in the brain. The author discusses thought patterns and how they tend to be organized by humans to group similar concepts together. A discussion of similarities in how the brain functions and how computers have been programmed is offered. The author concludes that more understanding of how human beings think could lead to better computer programming and more effective software.